The relationship between students' computer system skills and their readiness for using virtualization technology in learning at vocational college - Abdul Said Ambotang; Hairuddin Yakup (Global Academic Excellence, 2025)
This quantitative survey type study aims to examine the relationship between students' computer system skills and students' willingness to use virtualization technology in the learning process at the Vocational College in Tawau, Sabah. A total of 92 students in the vocational certificate and vocational diploma programs were selected as study respondents. Data was collected through the use of questionnaires and analyzed using descriptive statistics and inferential statistics using Statistical Software for Social Sciences (SPSS). The results of descriptive statistical analysis show that both students' computer system skills and their willingness to use virtualization technology are at a high level. Pearson Moment correlation analysis shows that there is a strong and significant relationship between the two variables. These results show that the higher the computer system skills and readiness of students, the more likely they will use virtualization technology in the learning process in vocational colleges. This study provides strong evidence that there is a significant positive relationship between students' computer system skills, their readiness, and the use of virtualization technology in the context of learning in a vocational college. Therefore, it is important for educational institutions to focus on the development of students' computer system skills and strengthen their readiness for the use of virtualization technology to increase the effectiveness of the learning process in this digital era.